Development of Entrepreneurs Health Interprofessional Collaboration (IPC) Empowerment - Wahyutri, Endah; Parelangi, Andi; Aransyah, Muhammad Fikry; Utami, Kurniati Dwi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Seeing the increasing unemployment rate of Poltekkes Kemenkes Kaltim graduates, the low motivation and interest of students in participating in business competitions such as Student Creativity, made the authors do this service. This service activity is important to increase participants' entrepreneurial insight through the Entrepreneurship Development Program (KDP). To foster a business spirit and entrepreneurial motivation through Interprofessional Collaboration (IPC) is the purpose of this activity, socialization of training and entrepreneurship assistance: marketing mix and Break Event Point (BEP). The method in this activity is through 5 steps: 1) socialization, 2) recruitment, 3) training, 4) practice, and 5) tenants independence this activity involves the ASI Support Group Community partners (KP ASI), independent practice midwives, and maternity clinics. The activity can be said to be successful because the predetermined target has been achieved. The results obtained from this activity are a) There tenants are 11recruitment products lagtogo and MPASI results from student research and student innovation, b) Knowledge of Marketing Mix and Break-Even Point (BEP), c) Making MOUs with 16 partners.